Potret Ideal Sikap Moderat Kiai di Era Millenial - Muhammad Idlom Dzulqarnain (UPT Pusat Studi Aswaja UNISNU Jepara, 2021)
AbstractThe problem of the breakdown of unity is a latent problem as well as a threat to the integrity of the nation. Ideological divisions and conflicts do not occur between religions, races, or groups.Splits and disintegration are also vulnerable to occur between religious leaders or kiai, andalsobetween students. Starting from the result of blind fanaticism, old-fashioned thinking, and lack of awareness of tolerance. Therefore, there needs to be an awareness of the kiai to be moderate. Because the kiai's thoughts have a lot of influence on theirstudents. This study aimedto analyze how the indicators of moderate, as well as the ideal portrait of the moderate attitude of the kiai. This study usedqualitative methods and descriptive analysis. The results of the study show that several indicators of moderate kiai can be mapped on four aspects. Firstly, the aspect of aqidah or ideology. The kiai in using arguments need to be balanced between naqli arguments and aqli arguments, so it is not easy to judge others wrong. Secondly, the social aspect. The kiai need to get along with all groups, prioritize common affairs, and peace. Thirdly, the cultural aspect. Kiai need to emphasize prevention rather than punishment with violence, democracyand get used to a culture of deliberation in deciding cases. A culture of tolerance while maintaining good old culture or methods, and remaining open to newness or technology. Fourthly, the national aspect. Kiai need to maintain the existence of national unity by upholding tolerance, respecting and obeying the government as long as it does not deviate from norms and religion, expresses opinions or criticisms to the authorities in a wise manner without violence.Keywords: kiai, moderation, pesantrenAbstrakProblem pecahnya persatuan menjadi masalah laten sekaligus ancaman keutuhan bangsa. Perpecahan dan konflik ideologi tidak hanya terjadi antar agama, ras, atau kelompok. Perpecahan dan disintegrasi juga rentan terjadi antar pemuka agama atau kiai, dan antar santri. Mulai dari akibat fanatisme buta, pemikiran yang kolot, dan kurangnya kesadaran toleransi. Oleh karena itu perlu ada kesadaran kiai untuk bersikap moderat. Karena pemikiran kiai memiliki banyak pengaruh terhadap para santri. Tujuan penelitian ini untuk menganalisis bagaimana indikator moderat, serta potret ideal sikap moderat kiai. Penelitian ini menggunakan metode kualitatif dan analisis deskriptif. Hasil penelitian menujukkan beberapa inidikator moderat kiai dapat dipetakan pada empat aspek. Pertama, aspek aqidah atau ideologi. Para kiai dalam menggunakan dalil perlu seimbang antara dalil naqli maupun dalil aqli,sehingga tidak mudah memvonis orang lain salah. Kedua, aspeksosial. Para kiai perlu bergaul dengan semua golongan, mengutamakan urusan bersama, dan perdamaian. Ketiga, aspek budaya. Kiai perlu menekankan preventif dari pada punishment dengan kekerasan, demokratis dan membiasakan budaya musyawarah dalam memutuskan perkara. Budaya toleransi dengan tetap menjaga budaya atau metode lama yang baik, dan tetap terbuka dengan kebaruan atau teknologi. Keempat, aspek kebangsaan. Kiai perlu menjaga eksistensi kesatuan bangsa dengan menjunjung sikap toleransi, menghormati serta menaati pemerintah selama tidak menyimpang dari norma dan agama, menyampaikan pendapat atau kritik kepada penguasa dengan cara bijak tanpa kekerasan.Kata Kunci: kiai, moderat, pesantren